Efeitos do 2,4-D sal colina e glufosinato de amônio em soja Enlist E3® - Lorscheiter, Arthur (2025)
The competition caused by weeds for natural resources is an obstacle in soybean cultivation. For this reason, it is sought to increase the tolerance of the crop to a range of herbicides, including the Enlist® technology, which allowed tolerance to the herbicides 2,4-D choline salt and glufosinate ammonium, in addition to glyphosate. However, the effects of phytotoxicity and on the yield components of soybean are not yet elucidated. In this context, the work aims to evaluate the effect of doses of 2,4-D and glufosinate ammonium, alone and in associations, in order to determine the application limit of these herbicides without causing phytotoxicity and negative impacts on the yield of the Enlist E3® soybean crop. Knowledge of these limits contributes to better management in the field. The experiment was carried out in a randomized block design with 4 replications, and the doses of 50, 100, 150, 200 and 250% of the active ingredient of the herbicides 2,4-D choline salt and glufosinate ammonium recommended by the package insert were studied, as well as the association of them at the doses of 50, 100 and 150% of the active ingredient of each herbicide. The herbicide application was carried out when the crop was in the phenological stage V3 and the variables evaluated were the severity of phytotoxicity (percentage of leaf area affected, after 7 days of application), grain yield (Kg.ha-1) and morphological components (plant height and insertion of the first vegetable, number of grains and legumes per plant, weight of a thousand grains). It was found that the treatments, despite causing different levels of phytotoxicity (up to 70% damage to the leaf area), did not alter the yield of grains and their components. These results may be associated with favorable weather conditions after herbicide application and during the crop cycle. It is recommended that, in addition to verifying the dose and active ingredient, herbicide applications in tolerant soybeans take into account climatic variables, always orienting themselves to use under conditions indicated by the package insert due to the effects of agrochemicals on the environment and safety of the applicator.